The Correlation between Family Support with Quality of Life Diabetes Mellitus Type 2 in Pademawu PHC - Wulan Meidikayanti; Chatarina Umbul Wahyuni (Jurnal Berkala Epidemiologi, 2017)
Diabetes Mellitus (DM) Type 2 is one type of DM that affects nearly 90% of patients with a diagnosis of DM in the world. DM type 2 patients need long-term care and treatment to prolong life and improve quality of life. This study aims to analyze the relationship of family support with the quality of life of patients with DM type 2. This type of research is observational analytic with a cross-sectional study design. The study population was all patients with DM type 2 who visited the Public health center (PHC) of Pademawu in May – June 2017. The number of samples was 50 respondents who were randomly selected using a simple random sampling technique. The variables studied were the characteristics of respondents (age, sex, level of education, length of suffering, complications), and family support. The results of the chi-square test with a significance level of 5% (α = 0.05) showed that variables significantly related to the quality of life DM type 2 were family support (p = 0.001) and DM complications (p = 0.011). The conclusion in this study is the variable of family support and complications have a significant relationship with the quality of life of DM type 2 in PHC of Pademawu, Pamekasan District so that health workers in PHC of Pademawu are expected to further enhance health promotion regarding the importance of family support to patients to extend the life of patients with DM type 2.